Involving hard-to-reach populations is pivotal for the tailoring and implementation of an epidemiological study in cross-border communities of French Guiana and Suriname - Schaub, Roxane; Ottevanger, M. Sigrid Mac Donald; Harkisoen, Soeradj; Pesna, Béatrice; Duijves, Celine; Heemskerk, Marieke; Polime, Thomas; Tuaillon, Edouard; Vreden, Stephen; Nacher, Mathieu (Frontiers in Public Health, 2023)
Background Hard-to-reach, vulnerable and cross-border populations are often disproportionately affected by communicable diseases. Epidemiological data on viral hepatitis in French Guiana and Suriname are available for urban areas, but not for remote communities. The Maroni River, which separates FG and Suriname, is home to Tribal and Indigenous communities. Reaching these populations is challenging due to logistical constraints, cultural and language barriers, and mistrust of outsiders. Objectives We aimed to conduct an epidemiological study of viral hepatitis [Maroni Hepatites Virales (MaHeVi)] in this remote and complex area. Here, we describe the operational hurdles and solutions required to achieve this. Methods We undertook a preliminary assessment of the area with local community leaders and health workers to gain approval of MaHeVi, acceptance of blood sampling, and suggestions for adapting the study to cultural and logistical constraints. Anthropological assessments were conducted through focus groups and interviews with key individuals to assess knowledge, beliefs and risk factors for VH. Results MaHeVi was well received by the local communities. The approval of the community leaders was crucial for the implementation and acceptance of the study. The main adaptations were hiring community health mediators to overcome cultural and language differences, using blotting paper instead of venipuncture for logistical and acceptability reasons, and adapting communication materials. Conclusion Careful preparation and tailoring of the communication materials and research protocol have enabled the successful implementation of the study. This process could be replicated in this area and transferred to other complex contexts combining borders, logistical hurdles and populations requiring cultural adaptations.